Perancangan Sistem Pengelolaan Sampah dengan Metode Material Flow Analysis (MFA) (Studi Kasus: Kota Tasikmalaya) - Detiar, Reki; Ulhasanah, Nova; Sari, Mega Mutiara (Journal of Sustainable Infrastructure, 2023)
This study concerns the design of a waste management system using the Material Flow Analysis (MFA) method in the city of Tasikmalaya. TPA Ciangir is the only landfill in Tasikmalaya, and its storage capacity has reached its maximum, necessitating improvements in waste management. The aim of this design is to determine an appropriate waste management system that can be implemented in Tasikmalaya. Based on observations and interviews, waste collection at TPA Ciangir in Tasikmalaya is conducted in small amounts, leading to a significant amount of household waste not being collected daily, resulting in waste accumulation and minimal transport to waste processing facilities. According to Permen PU Number 3 of 2013 and SNI 19-2454-2002, waste collection from the source should be conducted at least once every two days. Therefore, an evaluation and redesign of the waste management system based on technical aspects are needed. The best system selection will be carried out using the Analytical Hierarchy Process (AHP) method, which will then be recommended for application at TPA Ciangir in Tasikmalaya. Based on the calculations using the AHP method, scenario 3 scored the highest, at 1.676, using composting processes, RDF, and TPST-3R. From the design results, a total waste reduction of 81% was achieved, aligning with the government's target of a 70% waste reduction by 2020.